ESTUDO SOBRE A DESIGUALDADE DE RENDA E SEUS DETERMINANTES NO BRASIL - Jair Andrade de Araújo; Emerson Marinho (Revista de Políticas Públicas, 2015)
This work is viewed from panel data of Brazilian states towards the 1996-2009´s. It also aims to analyze the contribution concerning the different determinants for reducing Brazilian income inequality, which is estimated according to a survey called (PNAD). The idea here is using a dynamic econometric model which is estimated by the Method of Moments of the Generalized-System (MMG-system). The estimated results conclude that governmental income transferring did not have any impact upon the so-called dynamic concerning income inequality to the period sketched. However, if we consider other determinants, point out that education was the mainly contributor to reduce the income inequality. Furthermore, considers that the gross national product and the variable government’s tax burden contribute to increase income inequality in Brazil.